Manipulation of femtosecond laser filamentation by wire mesh amplitude mask - Geints, Yuri E.; Minina, Olga V.; Mokrousova, Daria V.; Pushkarev, Dmitrii V.; Rizaev, Georgy E.; Seleznev, Leonid V. (Optics Communications)
The results of numerical simulation on the propagation of high-power femtosecond laser pulses in air under conditions of the amplitude modulation are presented. Laser pulse amplitude modulation is realized by using the metal mesh-masks, which divide the initial laser beam into lower-energy parts (subbeams). We show that, in general, the beam energy partitioning by metal meshes reduces the total length of beam filamentation region in air, whereas the longitudinal continuity of the laser plasma distribution in the filaments is considerably improved. A strong dependence of the filamentation region parameters (starting coordinate, length, longitudinal continuity) on the position of the mesh-mask relative to the laser beam axis is also revealed. It turns out that under certain conditions, when the beam axis points to the mesh crossing, the spatial position of the filaments can be shifted further along the propagation path by increasing the size of the mesh cells. Alternatively, if the beam center exposes the mesh cell opening, the filamentation start coordinate decreases monotonically when the mesh becomes sparser. Additionally, the parameters of the filamentation region exhibit high sensitivity to the mesh wire thickness that can dominate the influence of mesh position and cell size.